Numerical Recursive Aggregation of VSC-Based Systems Using Impedance Modeling for Stability Analysis - Taleb Vahabzadeh; Seyyedmilad Ebrahimi; Juri Jatskevich (IEEE Open Journal of the Industrial Electronics Society)
The high penetration of voltage-source converter (VSC) based resources poses stability challenges to modern power systems due to introducing new dynamics with broad time-scale and frequency-coupling. The so-called impedance-based modeling (IBM) is widely used for the dynamic characterization and stability analysis of grid-connected VSCs. In this article, it is first shown that using IBM, the analytical aggregation of interconnected VSC-based systems results in very high-order transfer matrices, which are not conducive to stability analysis. As an alternative, a numerical recursive aggregation technique is proposed for interconnected VSC-based power systems. Using the proposed method, the individual multi-input multi-output transfer matrices of the IBM of VSCs can be readily used for aggregation across a range of discrete frequencies. Moreover, an algorithm is proposed to automate the aggregation of multiconverter-based systems. The proposed technique is illustrated on a VSC-based power system with multiple converters considering the interconnecting line impedances. The time-domain simulations and frequency analysis verify the accuracy and effectiveness of the proposed method, demonstrating that it is over 990 times computationally more efficient than the small-signal injection method for calculating the aggregated load admittance while also offering almost 80 times higher frequency resolution.